STRATEGI PENGEMBANGAN USAHA ATAP DAUN NIPAH (Nypa fruticans) DI KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG - Citra Vissilmi Qaffah Nasution; Supristiwendi Supristiwendi; Thursina Mahyuddin; Kiagus Muhammad Zain Basriwijaya (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to identify and analyze internal and external factors in the development of nipah leaf roofing businesses and formulate strategic priorities in the nipah leaf roofing business in Seruway District, Aceh Tamiang Regency. This research was conducted in Seruway District, Aceh Tamiang Regency. The sampling method used the census method with a sample of 25 people. To identify and analyze internal and external factors, as well as formulate strategic priorities in the development of a nipah leaf roofing business, a SWOT analysis with a qualitative approach is used to maximize strengths, weaknesses, opportunities, and threats. Data processing is done by EFI and EFE analysis, IE Matrix, SWOT Matrix, QSPM analysis. The results of this study indicate that the priority of the nipah leaf roof business development strategy obtained from the analysis using QSPM of the four alternative strategies obtained at the coordination stage is to inform about the product, create a cooperative relationship, so that it can form a management body or a group of craftsmen and minimize the risk. in Seruway District, Aceh Tamiang Regency.